Errata to the Review Article (Medit. Mar. Sci. 11/2, 2010, 381-493): "Alien species in the Mediterranean Sea by 2010. A contribution to the application of European Union’s Marine Strategy Framework Directive (MSFD). Part I. Spatial distribution" - ZENETOS, A.; GOFAS, S.; VERLAQUE, M.; CINAR, M.E.; GARCIA RASO, J.E; BIANCHI, C.N.; MORRI, C.; AZZURRO, E.; BILECENOGLU, M.; FROGLIA, C.; SIOKOU, I.; VIOLANTI, D.; et al. (Mediterranean Marine Science, 2011)
The state-of-art on alien species in the Mediterranean Sea is presented, making distinctions among the four subregions defined in the EU Marine Strategy Framework Directive: (i) the Western Mediterranean Sea (WMED); (ii) the Central Mediterranean Sea (CMED); (iii) the Adriatic Sea (ADRIA); and (iv) the Eastern Mediterranean Sea (EMED). The updated checklist (December 2010) of marine alien species within each subregion, along with their acclimatization status and origin, is provided. A total of 955 alien species is known in the Mediterranean, the vast majority of them having being introduced in the EMED (718), less in the WMED (328) and CMED (267) and least in the Adriatic (171). Of these, 535 species (56%) are established in at least one area. Despite the collective effort of experts who attempted in this work, the number of introduced species remains probably underestimated. Excluding microalgae, for which knowledge is still insufficient, aliens have increased the total species richness of the Mediterranean Sea by 5.9%. This figure should not be directly read as an indication of higher biodiversity, as spreading of so many aliens within the basin is possibly causing biotic homogenization. Thermophilic species, i.e. Indo-Pacific, Indian Ocean, Red Sea, Tropical Atlantic, Tropical Pacific, and circum(sub)tropical, account for 88.4% of the introduced species in the EMED, 72.8% in the CMED, 59.3% in the WMED and 56.1% in the Adriatic. Cold water species, i.e. circumboreal, N Atlantic, and N Pacific, make up a small percentage of the introduced species, ranging between 4.2% and 21.6% and being more numerous in the Adriatic and less so in the EMED. Species that are classified as invasive or potentially invasive are 134 in the whole of the Mediterranean: 108 are present in the EMED, 76 in the CMED, 53 in the Adriatic and 64 in the WMED. The WMED hosts most invasive macrophytes, whereas the EMED has the lion’s share in polychaetes, crustaceans, molluscs and fish.